Educating the Filipino Loob and Katwiran: Beyond the Impositions of a Cogito Rationality - Rodriguez, Agustin Martin G (Archīum Ateneo, 2023)
The Philippine educational system and its core curriculum is oriented toward the formation of the modern; autonomous; rational subject; particularly one that will fit into the contemporary global market and production system. Through this system; Filipinos are deepening the colonization of their rationalities and subjectivities by imposing a system that shapes a subject who exists to serve the global market by being a fit worker; consumer; entrepreneur; and producer of knowledge. However useful this educational system may be; it does not consider the “Filipino” subjectivity’s need for formation as a loob who is a kapwa. The Filipino subjectivity which is grounded on the experience of a loob filled with liwanag opening to the world; needs an education in its own capacity for knowing and realizing its well-being. The conception of the subject in relation to the world calls for a different kind of education; particularly in the development of indigenous skills in humanistic research. This paper will argue that as a Filipino student is subjected to the imposition of the dominant Western educational system; they should also equally be given an education in their own rationality rooted in their own native subjectivity . A people must have the opportunity to be trained in their own rationality rooted in their own subjectivity in order to evaluate its value for human flourishing.